2013
DOI: 10.1590/s0100-40422013000700014
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic effects of metabolites from Alternaria euphorbiicola against its host plant Euphorbia heterophylla

Abstract: Recebido em 20/11/12; aceito em 15/2/13; publicado na web em 24/5/13A bioassay-guided fractionation of culture filtrates of the fungus Alternaria euphorbiicola, a pathogen of the weed Euphorbia heterophylla, led to the isolation of anhydromevalonolactone (1), tyrosol (2), (R)-(-)-mevalonolactone (3), and cycloglycylproline (4). When tested on the punctured leaves of the host plant, these compounds produced bleached lesions with dark brown margins at concentrations as low as 80 µM. When tested on the leaves of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…The low effect verified may be related to the low concentration of metabolites present in fermented broth without the addition of adjuvant to improve the efficacy. Varejão et al (2013) reported that the phytotoxins are often present in low concentrations in the filtrate coming from the fermentation processes of microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…The low effect verified may be related to the low concentration of metabolites present in fermented broth without the addition of adjuvant to improve the efficacy. Varejão et al (2013) reported that the phytotoxins are often present in low concentrations in the filtrate coming from the fermentation processes of microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…23,24 Tyrosol has been isolated from various plant pathogenic fungi and is reported as a phytotoxic metabolite. [25][26][27] This is the first report of isolation of these two metabolites as phytotoxins from D. eres.…”
Section: N-(tert-butyl)-2-chloro-6-(2-hydroxy-2-methylpropyl)-3-methyl-mentioning
confidence: 99%
“…(3), 22 and (R)mevalonolactone (4), 23,24 respectively. Their identification was confirmed by the HRESIMS spectra and for were very similar to those reported in literature for the natural epi-dihydropyriculol 21 and (R)-mevalonolactone, 23 respectively.…”
Section: Resultsmentioning
confidence: 99%